A Survey of Women and Their Providers Regarding Gestational Weight Gain Across the United States [31C]. (May 2018) - Power, Michael L.; Gaspar-Oishi, Maria; Gibson, Kelly S.; Rhoades, Courtney; Turrentine, Mark; Yamamura, Yasuko; Mackeen, A. Dhanya
Abstract : INTRODUCTION: Assess patient and provider knowledge and opinions about gestational weight gain (GWG) particularly in relation to the Institute of Medicine (IOM) guidance with respect to maternal body mass index (BMI). METHODS: Questionnaires were distributed by medical centers across the United States to patients (8 sites) and providers (7 sites). Data on maternal BMI and GWG was collected at all sites. RESULTS: 1, 157 women returned questionnaires (1, 820 maximum possible). A majority at all sites reported a provider discussed their expected GWG with them. Close to half reported that a provider had discussed potential harms from inappropriate GWG. Most of the women (71.2%) considered their obstetrician to be a helpful resource for GWG advice. Most providers (87.5%) reported they were aware of the IOM guidelines. As many providers disagreed (18.8%) as agreed (20.8%) that they were successful at helping their patients gain an appropriate amount of weight during pregnancy (58.3% were neutral). Physician self-reported confidence was associated with their opinions on whether they could help their patients avoid excessive GWG. The most common outcome at all sites was GWG above the IOM recommendations. Overweight and obese women were more likely to gain above recommendations. Providers underestimated the proportion of their patients that gained below recommendations (8.5% versus 18.9%). CONCLUSION: Providers are aware of the dangers of excessive GWG and are counseling patients. Providers appear more cognizant of excessive GWG and underestimate the proportion that may have inadequate GWG. Most women are not achieving an appropriate GWG, especially overweight and obese women.